Overview of Suicide Risk in Elderly at Nursing Home of Jember - Prasasti Puspita Avcafebriliani; Latifa Aini Susumaningrum; Tantut Susanto; Hanny Rasni; Fahruddin Kurdi (KHD-Production, 2023)
The risk of suicide is one of the most vulnerable nursing problems experienced by the elderly. The risk of suicide occurs because of several suicide risk factors experienced by the elderly. This study aims to describe the risk of suicide in the elderly at UPT PSTW (nursing home) Jember. The research design used is a descriptive survey. The sampling technique used is total sampling. The sample used in this study was 76 elderly who were selected based on inclusion and exclusion criteria. Data were collected using the Geriatric Suicide Ideation Scale (GSIS) questionnaire to determine the risk of suicide in the elderly. The One Sample Kolmogorov-Smirnov test was used to achieve the objectives of this study. The results showed that the elderly experienced a significant risk of suicide but in the low category Md (P25-75)= 62(60-65); Z=0.151; p-value=0.000. This study concludes that there is a significant risk of suicide in the elderly at UPT PSTW Jember. Therefore, it is necessary to increase the spirit of life for the elderly by always reminding the elderly that there is still life and hope for them.